An asymmetrical dual coating on the stent prepared by ultrasonic atomization. Issue 3 (8th October 2018) - Wang, Jingjing; Ren, Yuzhen; Huang, Yuhua; Du, Ruolin; Xi, Yadong; Yin, Tieying; Wang, Yazhou; Zhang, Dechuan; Chen, Jinju; Wang, Guixue
Abstract: This study aims to design an asymmetric dual coating (ADC) on the stent by ultrasonic atomization to solve the problem of delayed endothelialization and late or very late stent thrombosis which caused by drug eluting stent (DES) with symmetric coating. Chitosan‐loaded monoclonal platelet glycoprotein IIIa receptor antibody SZ‐21 coating (CSC) was sprayed on inner surface of stents, and outer surface was sprayed CSC and poly(lactic‐co‐glycolic acid) (PLGA) loaded with docetaxel (DTX) coating (PDC). The coated surface was uniform without aggregation and no shedding phenomenon either before or after stent expanded. Fluorescence labeling has confirmed that the coating has an asymmetric structure. The cumulative release for SZ‐21 and DTX was 40.11% and 27.22% within first 24 h, then DTX became the major released drug from 24 h to 7 d, after released for 28 d about 40% of the SZ‐21 and 50% DTX still remained on the coated stent. It achieved that ADC can inhibit thrombosis at earlier period and inhibit vascular smooth muscle cells (VSMCs) proliferation at later period. And that ADC has good hemocompatibility and can significantly inhibit VSMCs proliferation. Finally, 4 and 12 weeks after the stent with ADC implanted into rabbit carotid arteries, it showed that the stent with ADC was safe and could effectively prevent thrombosis and in‐stent restenosis. © 2018 Wiley Periodicals, Inc. J. Biomed. Mater. Res. Part B, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 825–837, 2019.